Regional‐scale patterns of soil microbes and nematodes across grasslands on the Mongolian plateau: relationships with climate, soil, and plants. Issue 6 (20th November 2014) - Chen, Dima; Cheng, Junhui; Chu, Pengfei; Hu, Shuijin; Xie, Yichun; Tuvshintogtokh, Indree; Bai, Yongfei
<x xml:space="preserve">Abstract</x> Belowground communities exert major controls over the carbon and nitrogen balances of terrestrial ecosystems by regulating decomposition and nutrient availability for plants. Yet little is known about the patterns of belowground communities and their relationships with environmental factors, particularly at the regional scale where multiple environmental gradients co‐vary. Here, we describe the patterns of belowground communities (microbes and nematodes) and their relationships with environmental factors based on two parallel studies: a field survey with two regional‐scale transects across the Mongolia plateau and a water‐addition experiment in a typical steppe. In the field survey, soils and plants were collected across two large‐scale transects (a 2000‐km east–west transect and a 900‐km south–north transect). At the regional‐scale, the variations in soil microbes (e.g. bacterial PLFA, fungal PLFA, and F/B ratio) were mainly explained by precipitation and soil factors. In contrast, the variation in soil nematodes (e.g. density of trophic groups and the bacterial‐feeding/fungal‐feeding nematode ratio) were primarily explained by precipitation. These variations of microbe or nematode variables explained by environmental factors at regional scale were derived from different vegetation types. Along the gradient from nutrient‐poor to nutrient‐rich vegetation types, the total variation in soil microbes explained by precipitation increased and that explained by plant and soil decreased, while the opposite was true for soil nematodes. Experimental water addition, which increased rainfall by 30% during the growing season, increased biomass or density of belowground communities, with the nematodes being more responsive than the microbes. The different responses of soil microbial and nematode communities to environmental gradients at the regional scale likely reflect their different adaptations to climate, soil nutrients, and plants. Our findings suggest that the soil nematode and microbial communities are strongly controlled by bottom‐up effects of precipitation alone or in combination with soil conditions.